Putting a Teaspoon of Programming into Other Subjects: Using teaspoon languages to integrate programming across myriad academic disciplines. - Guzdial, Mark; Dodoo, Emma; Naimpour, Bahare; Nelson-Fromm, Tamara; Padiyath, Aadarsh (Communications of the ACM, 2023)
The article looks at the introduction of computer programming into high school classes other than mathematics or computer science classes, focusing on the authors' project of creating Task-Specific Programming (TSP) languages, also called teaspoon languages, that teachers and students in classes such as history can learn quickly and then use for tasks related to their subject. They note that TSP languages are a type of domain-specific programming languages (DSLs).